The Effect Of MSG (Monosodium Glutamate) And Origin Of Stem Cutting On Growth Moringa Olifera (Moringa) Plant Seeds - Yususf, Mukhtar; Susanti, Rini (Talenta Publisher, 2020)
Moringa olifera is known worldwide as a nutritious plant and WHO has introduced Moringa as an alternative food to overcome nutritional problems (malnutrition). Moringa plants are sought after because they can be processed into a variety of herbal medicines to raw materials for skincare products.